New classification of EAONO/JOS cholesteatoma and SAMEO-ATO middle ear surgery: relevance and clinical significance - Ekaterina V. Pchelenok; Olga Yu. Tarasova; Sergey Ya. Kosyakov (ZAO "Consilium Medicum", 2021)
Middle ear cholesteatoma (MEC) is a common problem of modern otology. The European Academy of Otology and Neurootology in cooperation with the Japanese Otological Society (EAONO/JOS) published consensus recommendations on the definition, classification and stages of MEC in 2017. In 2018, the classification of middle ear surgery was presented under the auspices of the International Otology Outcome Group. The leading problem of MEC surgery remains the high recurrence rate, which ranges from 5 to 32% depending on the type of surgical intervention. The main purpose of this article is to describe the new EAONO/JOS classification of MEC and SAMEO-ATO middle ear surgical interventions with an analysis of their possible clinical significance in determining the risk of cholesteatoma recurrence as well as the prognosis for hearing recovery after surgery.